KETERBATASAN PERAN DEWAN PERWAKILAN DAERAH DALAM REPRESENTASI KEPENTINGAN DAERAH - Romadhon, Ahnaf Nur Fauzan (Jurnal JURISTIC, 2024)
This study analyzes the limited authority of the Regional Representative Council (DPD) in representing regional interests within Indonesia's constitutional framework. Despite DPD's intended role as a body to represent local concerns at the national level, its legislative and oversight powers are highly restricted, allowing only proposals and considerations on specific legislative matters. This limitation significantly impacts DPD’s effectiveness in advocating for local aspirations, as seen in several legislative proposals that failed to progress within the national legislative program (Prolegnas) for 2015-2024. Using a normative juridical approach with literature review, this research identifies key issues arising from DPD’s constrained role, comparing it with other bicameral systems where both chambers hold equal legislative powers. The study highlights the need for constitutional reform to strengthen DPD’s role, suggesting that empowering DPD with decision-making rights could enhance regional representation and foster a more balanced bicameral system in Indonesia.